Ballad: Ballade, Complainte, Chanson Tragique, Chanson Lyrico-Épique ou Chanson Narrative? - Paquin, Robert (MUSICultures, 1980)
In Anglo-American folklore studies, and in Europe in general, the ballad is a well defined genre. Not so in French. While English-speaking folklorists agree that the ballad is a narrative folk song with formal characteristics which set its meter and stanzaic shape apart from other types of folk songs, French folk specialists have never defined one particular folk genre as precisely as this, and have mostly been concerned with collecting and cataloguing all types of songs in terms of their theme, subject matter, style, object, use, age, origin, or other. Even if French scholars do use such terms as “complaintes,” “chansons tragiques,” or “chansons lyricoepiques” which seem to correspond to the English "ballads,” no two scholars use any of those terms with the same definition, and never does it correspond exactly to the ballads. A whole field of study is therefore open to enterprising French folk researchers who would wish to isolate French narrative folk songs, call them “ballades folkloriques” to distinguish them from the literary “ballades,” and describe their formal characteristics. Such a study would lead to rewarding comparative studies, especially between French and English ballads in Canada, for example.